Enemies in Neoliberalism and the Schmittian friend/foe opposition - Pierre Dardot (Geografares, 2022)
Transcript of the author's exhibition at the GENA Study Day, on May 30, 2022 at the National Conservatory of Arts and Crafts (CNAM), Paris.
Keywords: Carl Schmitt; neoliberalism; enemy instantiation; decision; civil war